Determination of chemical composition and structural changes of torrefied Leucaena leucocephala (petai belalang) pellets via TAPPI method/FTIR: article - Nor Azizan, Nor Atiqah; Puasa, Siti Wahidah; Matali, Sharmeela (2018)
Alternative energy from renewable resources such as biomass can be used as a substitution to fossil fuel for a greener energy option. However, utilization of biomass has some limitations such as high ash and moisture content, low energy density, low heating value, and high energy is required for size reduction. Torrefaction which is also known as a mild pyrolysis pre-treatment can be implemented to upgrade the physical and chemical properties of biomass. This pre-treatment involves a moderate temperature above 200°C in the absence of oxygen. Torrefaction offers advantages in overcoming the problem arise associated with raw biomass. In this study, a potential energy crop, Leucaena leucocephala, a woody biomass will be studied for its energy purposs as to identify their potential usage as bioenergy fuel. The purpose of this study was to determine the chemical composition and structural changes of torrefied Leucaena leucocephala pellets by using TAPPI method and FTIR. The torrefaction process of the sample was conducted in a horizontal tube furnace at five different temperatures with 60 min of holding time. The chemical compositions and structural changes of torrefied products were compared to its raw forms. The results obtained show a decrease in cellulose and hemicelluloses and an increase in lignin content as torrefaction temperature became severe. It was concluded that as torrefaction temperature increases, high quality of biomass with low moisture and volatiles content was produced. The results obtained prove that torrefaction as pretreatment process improves the biomass properties.